Immunity, infectious diseases and the knowledge of 100 Latvian pregnant women of the impact of infectious diseases on the pregnancy and its prevention - Abramova, Anna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Infection diseases may adversely affect the pregnancy, lead to the development of foetal abnormalities, foetal death, congenital infections and preterm birth. Infection is possible in antenatal, postnatal and intranatal way. CMV, adenovirus, enterovirus are the most common viruses which are found during the examination of amniotic fluid. Hundred Latvian pregnant women were offered to fill in the questionnaire with the help of which it will be possible to study their knowledge on infectious diseases during pregnancy and preventive options. The obtained data were compared with foreign literature and foreign studies. Respondents’ age was from 19 to 43 years. Only 65% of women are aware that the risk of contracting infectious diseases during pregnancy is higher. Only 7% of women know about all possible ways of infection during pregnancy. 68% of women note that bacterial vaginosis may harm foetus and adversely affect pregnancy. Compared to the study conducted in Japan, Latvian pregnant women know about toxoplasmosis 4% more often than in Japan. Knowledge of pregnant women about the impact of infectious diseases on the foetus and pregnancy, potential infection and prevention ways is insufficient. Women want to know and receive understandable information from health care professionals.